The Ability of Lipoprotein (a) Level to Predict Early Carotid Atherosclerosis Is Impaired in Patients With Advanced Liver Fibrosis Related to Metabolic-Associated Fatty Liver Disease. Issue 7 (23rd July 2022) - Wu, Tingfeng; Ye, Junzhao; Shao, Congxiang; Lin, Yansong; Wang, Wei; Feng, Shiting; Zhong, Bihui
Abstract : INTRODUCTION: Hepatic fibrosis reduces the serum level of lipoprotein (a) (Lp(a)) and may affect its accuracy in cardiovascular disease prediction of metabolic-associated fatty liver disease (MAFLD). We aimed to estimate the association between Lp(a) levels and the risk of carotid atherosclerosis in MAFLD patients with advanced fibrosis. METHODS: This was a cross-sectional study enrolling 4, 348 consecutive individuals (1, 346 patients with MAFLD and 3, 002 non-MAFLD patients) who were admitted to the First Affiliated Hospital, Sun Yat-sen University, and underwent abdominal and carotid ultrasonography from 2015 to 2021. Lp(a) levels, liver biochemical markers, metabolic indices, and anthropometric parameters were measured. Liver fat content and fibrosis severity were assessed by MRI-PDFF, using the NAFLD fibrosis score (NFS) and liver stiffness measurement (LSM) of two-dimensional shear wave elastography, respectively. RESULTS: There was an L-shaped relationship between Lp(a) levels and LSMs in patients with MAFLD, and Lp(a) levels had a different relationship with liver fat content in MAFLD patients with F1-2 versus those with F3-4. Non-MAFLD patients had higher levels of Lp(a) than MAFLD patients with or without advanced fibrosis (both P < 0.05). Lp(a) levels and degree of liver fibrosis were both positively correlated with carotid atherosclerosis in patients with MAFLD. Lp(a) levels performed well on carotid atherosclerosis risk prediction for non-MAFLD patients with an area under the curve (AUC) of 0.819, which was significantly better than the carotid atherosclerosis risk prediction for MAFLD patients with NFS ≤ −1.836 (AUC: 0.781), NFS > −1.836 (AUC: 0.692), and LSM ≥ 9.0 kPa (AUC: 0.635) (all P < 0.05). DISCUSSION: Advanced liver fibrosis significantly reduces the predictive value of Lp(a) levels for the risk of carotid atherosclerosis in patients with MAFLD. Abstract :